A148 IMPACT OF EXAMINATION UNDER ANESTHESIA PRIOR TO ANTI-TUMOR NECROSIS FACTOR THERAPY ON FISTULA HEALING FOR PERIANAL CROHN'S DISEASE PATIENTS: A COMPARATIVE COHORT STUDY. (21st February 2022) - Fung, M; Chan, M; Chin Koon Siw, K; Sabri, E; McCurdy, J
Abstract: Background: Current guidelines recommend a combined approach consisting of an examination under anesthesia (EUA) and anti-TNF therapy for perianal Crohn's Disease (PCD). However, the impact of this approach on fistula healing and long-term outcomes is unknown. Aims: To assess the effect of EUA on fistula healing and long term outcomes in patients with perianal Crohn's disese who are treated with anti-TNF therapy. Methods: We performed a retrospective, single-center, comparative cohort study between 2009 and 2019. We compared patients with PCD who received EUA prior to anti-TNF therapy (combined therapy) to anti-TNF therapy alone. Our primary outcome was fistula closure by clinical assessment. Secondary outcomes included subsequent local surgery and fecal diversion. Logistic regression and multivariable cox-proportional hazard models adjusted for abscesses, concomitant immunomodulators, and time to anti-TNF initiation were performed. Results: A total of 155 patients underwent 188 distinct anti-TNF starts: 66 (35%) after an EUA. Patients who underwent an EUA prior to anti-TNF therapy were more likely to have an abscess (50% vs. 15%; p < 0.001) and concomitant immunomodulator usage (64% vs. 50%; p = 0.07). Otherwise, there were no differences between cohorts in age, smoking status, disease duration, and location of luminal disease. There were no significant differences in fistula closure at 3, 6, or 12 months between cohorts overall (Table 1). The results remained consistent in sensitivity analyses that excluded patients with abscesses and prior biologic treatment failure. The results were also similar when defining the combined therapy group as those with setons. After a median follow-up of 4.6 years (IQR, 5.95) patients who underwent an EUA prior to anti-TNF therapy were more likely to require a subsequent EUA (aHR 2.2; 95% CI, 1.3–3.6) (Figure 1) but not fecal diversion (aHR 1.3; 95% CI, 0.45–3.9). Conclusions: In this single center study, combined therapy (EUA prior to anti-TNF therapy) was not associated with improved clinical outcomes compared with anti-TNF therapy alone. These findings suggest that EUA may not be necessary in every patient with PCD prior to initiation of anti-TNF therapy. Future prospective studies that control for fistula complexity are warranted. Table 1: Unadjusted rates of fistula closure after anti-TNF therapy comparing patients with and without an exam under anesthesia Funding Agencies: University of Ottawa Department of Medicine